Studi Pencampuran Batubara untuk Memenuhi Permintaan Konsumen di PT Bukit Baiduri Energi, Kutai Kartanegara, Kalimantan Timur - Ferry Potik Kurniawan; Agus Winarno; Henny Magdalena; Windhu Nugroho; Rety Winonazada (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The coal blending process conducted by PT. Bukit Baiduri Energi (PT. BBE) aims to achieve coal quality specifications that align with customer requirements. PT. BBE possesses multiple coal seams with varying quality characteristics, necessitating a carefully planned blending system with precise proportions to produce coal products that meet market demands. The objectives of this study are: to plan the quantity and quality parameters for coal blending, to evaluate the actual outcomes of coal blending in terms of quantity and quality, and to identify the factors contributing to discrepancies between the planned and actual coal quality following the blending process. To determine the optimal quantity and quality of each coal product in the blending plan, the simplex method was employed with the assistance of POM-QM for Windows version 5 software, alongside the weighting factor method. The final coal blending plan resulted in a total of 55,000 MT with the following quality specifications total moisture of 20.00% (ar), ash content of 6.10% (ad), total sulfur of 1.65% (ad), and a calorific value of 5,350 kcal/kg (ad). The actual blending outcome yielded the same quantity of 55,000 MT, with quality parameters as follows: total moisture of 20.18% (ad), ash content of 5.60% (ad), total sulfur of 1.35% (ad), and a calorific value of 5,340 kcal/kg (ad). The analysis of quality discrepancies revealed several contributing factors the presence of water accumulation in the ROM Stockpile following rainfall, which increased total moisture, the inadvertent inclusion of foreign materials into the feeder, resulting in elevated ash content, the unintentional mixing of coal from different product types, which led to inconsistencies in total moisture, ash content, total sulfur, and calorific value, and the rise in total moisture, which adversely affected the calorific value.